2023
DOI: 10.3390/ijms24065410
|View full text |Cite
|
Sign up to set email alerts
|

The P2X7 Receptor as a Mechanistic Biomarker for Epilepsy

Abstract: Epilepsy, characterized by recurrent spontaneous seizures, is a heterogeneous group of brain diseases affecting over 70 million people worldwide. Major challenges in the management of epilepsy include its diagnosis and treatment. To date, video electroencephalogram (EEG) monitoring is the gold-standard diagnostic method, with no molecular biomarker in routine clinical use. Moreover, treatment based on anti-seizure medications (ASMs) remains ineffective in 30% of patients, and, even if seizure-suppressive, lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 151 publications
0
8
0
Order By: Relevance
“…Adenosine metabolized from released ATP in the extracellular space activates both anticonvulsive A1 and proconvulsive A2A receptors [76][77][78]. Therefore, purinergic transmission functions are a double-edged sword in terms of the epileptogenesis/ictogenesis regulation of the excitatory/inhibitory balance of tripartite synaptic transmission [6,7,79,80]. To explore the functional abnormalities of purinergic transmission in S286L-TG, age-dependent extracellular levels of ATP and adenosine in the ADSHE focus region of S286L-TG should be determined using microdialysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adenosine metabolized from released ATP in the extracellular space activates both anticonvulsive A1 and proconvulsive A2A receptors [76][77][78]. Therefore, purinergic transmission functions are a double-edged sword in terms of the epileptogenesis/ictogenesis regulation of the excitatory/inhibitory balance of tripartite synaptic transmission [6,7,79,80]. To explore the functional abnormalities of purinergic transmission in S286L-TG, age-dependent extracellular levels of ATP and adenosine in the ADSHE focus region of S286L-TG should be determined using microdialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, functional abnormalities in tripartite synaptic transmission or astroglial excitatory transmission have been considered to play important roles in the development of epileptogenesis and/or ictogenesis [1][2][3][4][5][6][7][8]. Functional abnormalities of astroglial hemichannels containing connexin43 [9][10][11][12][13] have been demonstrated in a validated genetic rat model of autosomal dominant sleep-related hypermotor epilepsy (ADSHE), named "S286L-TG"; it bears the missense S286L-mutant rat Chrna4, which corresponds to the S284L-mutant human CHRNA4 of patients with ADSHE [8,14].…”
Section: Introductionmentioning
confidence: 99%
“…The P2X7R (purinergic ligand-gated ion channel 7 receptor), an ATP-gated cation non-selective channel receptor, is a crucial contributor to the formation and release of IL-1β and has been widely considered an essential target in brain tissue inflammatory responses 5 . P2X7R is upregulated at different stages of seizure In various models of epilepsy, including the hippocampus, amygdala, piriform cortex, and neocortex, and its activation can induce and worsen inflammatory reactions 6 . Multiple studies 7,8 have demonstrated that in innate myeloid cells such as monocytes, macrophages, and dendritic cells, the P2X7R is the most effective activator of the NLRP3 inflammasome during the inflammatory process.…”
Section: Introductionmentioning
confidence: 99%
“…Research over recent decades has provided compelling proof that purinergic signalling via the adenosine 5'-triphosphate (ATP)-gated cationic P2X7 receptor (P2X7R) is implicated not only in the generation of seizures (ictogenesis), but also epilepsy [8,22]. While several reviews published over recent years have provided a detailed summary of the data demonstrating a role for P2X7Rs during seizures and epilepsy (e.g., [8,[22][23][24][25][26][27][28]), we here will focus on how drugs targeting the P2X7R may be used in a clinically relevant setting.…”
Section: Introductionmentioning
confidence: 99%